World Potential of Natural Resources and Problem for Efficient Use of Resources - IUDINA, Svetlana V.; ANTIPOVA, Olga; KISELEVA, Olga V. (Journal of Environmental Management and Tourism, 2017)
Great interest to the concept, principles, and tools of efficient use of resources is caused not only and not so much by “the fashion” for so called tactical anti-crisis measures but by the strategic necessity to provide the resources base of the real sector of economy in the long-term perspective. Sometimes advantageous environment quickly disrupts stable growth during the period. The analysis of data shows that in spite of the vector of energy efficiency and reasonable use of raw materials declared in separate economies their world consumption grows on the background of the decreasing reserves. The authors of this research offer a multilevel (three-stage) system of energy efficiency management. It can become the basis of the national economic strategy of providing future generations with resources because it focuses the managing impact, above all, on the regional level and thereby it gives it “the operating” tone.